Towards Safer Rail Travel: A Study on CCTV Coverage and Utilization Onboard Trains - ALIAH NADHIRAH; Karthigesu A/L Nagarajoo; Nur Amira Mohamad Yusoff (Progress in Engineering Application and Technology, 2025)
The increasing demand for safety and security in railway systems has led to the widespread adoption of Closed-Circuit Television (CCTV) surveillance. This project examines the effectiveness and optimization of CCTV surveillance coverage in railway environments, addressing the critical need for robust monitoring solutions in public transportation. The methodology encompasses a comprehensive approach that includes data collection through surveys, incident reports, and video footage analysis; the design of an optimized CCTV system utilizing advanced camera selection and placement strategies; and the implementation of real-time monitoring tools integrated with machine learning algorithms for enhanced anomaly detection. Performance evaluation metrics such as incident response times and crime rate reductions are established to assess the system’s impact post-installation. Furthermore, a continuous improvement framework is proposed to ensure the system adapts to evolving security challenges and technological advancements. By systematically evaluating and optimizing CCTV coverage, this project aims to enhance passenger safety and bolster public confidence in railway travel, ultimately contributing to a more secure transportation infrastructure.